2010
DOI: 10.1002/adfm.201001521
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in Dye‐Sensitized SnO2 Nanowire Field‐Effect Transistors

Abstract: Electron transfer from excited dye molecules (chlorophyll or fluorescein) to a semiconductor is demonstrated by photoaction and photoluminescence spectra on field‐effect transistors consisting of dye‐sensitized individual SnO2 nanowires. The photoaction spectrum shows a much better resolution for nanowires non‐covalently functionalized with dye molecules than for dyes deposited on SnO2 nanoparticle‐films. Possible reasons for the deviation between the photoaction spectra and ordinary optical absorption spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Because electron-hole pairs are generated in the Chla molecules under illumination, the PL quenching suggest that charge transfer occurs between the Chla film and graphene, which leads to reduction of radiative recombination. [40] Moreover, the back-gate dependence of the photoresponse (Figure 2f) is also consistent with the proposed model. We observed a strong carrier type and concentration dependence of the photocurrent ( By contrast, the photoinduced hole carriers diminish the electron concentration, which leads to a decreased conductance and a negative I Δ in the electron conduction regime (…”
Section: Resultssupporting
confidence: 86%
“…Because electron-hole pairs are generated in the Chla molecules under illumination, the PL quenching suggest that charge transfer occurs between the Chla film and graphene, which leads to reduction of radiative recombination. [40] Moreover, the back-gate dependence of the photoresponse (Figure 2f) is also consistent with the proposed model. We observed a strong carrier type and concentration dependence of the photocurrent ( By contrast, the photoinduced hole carriers diminish the electron concentration, which leads to a decreased conductance and a negative I Δ in the electron conduction regime (…”
Section: Resultssupporting
confidence: 86%
“…The process is complemented by the slower back-transfer of electrons from the conduction band (CB) of ZnO to the highest occupied molecular orbital (HOMO) energy level of D102. 11 The photoinduced charge will also drift to the dielectric (SiO 2 )/ZnO interface under applied gate bias, inducing a significant increase in the surface charge in the channel. According to the gradual channel approximation model, the threshold voltage of the transistor is directly proportional to the surface charge density and will hence be shifted accordingly, in excellent agreement with the current observation.…”
Section: Resultsmentioning
confidence: 99%
“…The effect was attributed to charge transfer from the dye to SnO 2 NWs upon illumination. 11 Using a slightly different approach, Yan et al reported high performance phototransistors based on blends of an organic semiconducting polymer, as the donor, and TiO 2 nanoparticles as the acceptor component. 12,13 Despite its preliminary stage, this early work demonstrates the potential of metal oxide-organic hybrid systems for the development of novel device concepts with tailored optoelectronic characteristics.…”
mentioning
confidence: 99%
“…Metal oxides are prospective materials for applications in various fields such as solar energy conversion, photocatalysis, electrochemical catalysis, lithium/sodium ion batteries, field effect transistors and super capacitors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and have been intensively studied due to their inherent chemical stability, abundance, low cost and environmental friendliness. Metal oxide nanostructures are being widely used in place of bulk counterparts as the unique morphology, surface structure and optoelectronic characteristics associated with the nanostructures are uniquely enhancing the performance devices.…”
Section: Introductionmentioning
confidence: 99%